IDENTIFICATION AND IMITATION ARE THE QUALITY OF MOTIVATION FOR CAREER CHOICE OF TEENAGERS - Ж. Зайнобидинов (Journals Park Publishing, 2023)
The article is devoted to the problem of the phenomenon of identification affecting the process of choosing a profession of students of adolescent age, it describes the phenomenon of identification, its appearance and types in adolescents, and the concept of professional-pedagogical identification.
Keywords: Identification, teenagers, choice of profession, imitation motive, professional-pedagogical identification.